Olefinic vs aromatic way of substituent effects: The case of 3‐ and 4‐substituted cyclohexa‐1, 3‐dienamine derivatives. (28th February 2017) - Szatylowicz, Halina; Siodla, Tomasz; Krygowski, Tadeusz M.
Abstract: Quantum chemical modeling was used to confront substituent effects in olefinic systems with an analogous situation in benzene. The B3LYP/6‐311++G(d, p) method was applied to examine electron‐donating properties of the amino group in a series of 3‐ (meta‐like) and 4‐ (para‐like) X‐substituted cyclohexa‐1, 3‐dienamines (X = NMe2, NH2, OH, OMe, Me, H, F, Cl, CF3, CN, CHO, COMe, CONH2, COOH, NO2, NO). As in the case of substituted anilines (PCCP, 2016, 18, 11711), the substituent properties were described by σ, charge of the substituent active region(X), and substituent effect stabilization energy descriptors; the amino group was characterized by structural and electronic parameters, whereas a transmitting moiety—by aromaticity index harmonic oscillator model of aromaticity. All applied substituent properties parameters were found to be mutually interrelated, with much better correlations for the para‐derivatives than the meta‐derivatives. Electron‐donating ability of the amino group is stronger affected (circa 1.4 times) by substituent acting from position 4 in cyclohexa‐1, 3‐dienamines than in aniline derivatives. It was also numerically confirmed that the reverse substituent effect acting to para‐position is stronger (circa 1.14 times) in olefinic systems than in aromatic ones. Moreover, for 1‐4 interactions, an increase of the electron‐attracting power of the substituent increases π‐electron delocalization in the olefinic series, whereas decreases it in the aromatic ones. Abstract : Both classical and reverse substituent effects acting from para‐position are always stronger in olefinic systems than in aromatic ones. Moreover, for 1‐4 interactions the substituent effect on π‐electron delocalization in diene systems is opposite to that observed in aromatic ones—an increase of the electron‐attracting power of the substituent increases π‐electron delocalization in the olefinic series, whereas decreases it in the aromatic ones.